Dataset associated with "Analysis of Kenya's Atmospheric Moisture Sources and Sinks" - Keys, Patrick W. (Colorado State University. Libraries, 2022)
Achievement of the United Nations Sustainable Development Goals (SDGs) are contingent on understanding the potential interactions among human and natural systems. In Kenya, the goal of conserving and expanding forest cover to achieve SDG 15 ‘Life on land’ may be related to other SDGs because it plays a role in regulating some aspects of Kenyan precipitation. We present a 40-year analysis of the sources of precipitation in Kenya, and the fate of the evaporation that arises from within Kenya. Using MERRA2 climate reanalysis and the Water Accounting Model 2-layers, we examine the annual and seasonal changes in moisture sources and sinks. We find that most of Kenya’s precipitation originates as oceanic evaporation, but that 10% of its precipitation originates as evaporation within Kenya. This internal recycling is concentrated in the mountainous and forested Kenyan highlands, with some locations recycling more than 15% of evaporation, to Kenyan precipitation. We also find that 75% of Kenyan evaporation falls as precipitation elsewhere over land, including 10% in Kenya, 25% in the Democratic Republic of the Congo, and around 5% falling in Tanzania and Uganda. Further, we find a positive relationship between increasing rates of moisture recycling and fractional forest cover within Kenya. By beginning to understand both the seasonal and biophysical interactions taking place, we may begin to understand the types of leverage points that exist for integrated atmospheric water cycle management. These findings have broader implications for disentangling environmental management and conservation and have relevance for large-scale discussions about sustainable development.
The data are a gridded set of files that contain data on the evaporative sources that provide precipitation to Kenya, and the destinations to which Kenya's evaporation will later fall as precipitation. The data are further described in the README document and the original publication.
School of Global Environmental Sustainability
Department of Ecosystem Science and Sustainability
Department of Atmospheric Science
Keywords: climate services; land-atmosphere interactions; water vapor; water cycle; Africa; sustainability